Parents' Experience and Satisfaction in Neonatal Intensive Care Units in Ethiopia: A Multicenter Cross-Sectional Study Using an Adapted Version of EMPATHIC-N - Gulo, Berhanu; Miglierina, Laura; Tognon, Francesca; Panunzi, Silvia; Tsegaye, Ademe; Asnake, Tina; Manenti, Fabio; Dall'Oglio, Immacolata (Frontiers in Pediatrics, 2021)
Background: In neonatal intensive care units (NICU) setting, parents' experience and satisfaction permit to evaluate clinical practice and improve the care of infants and parents. Little is known about this topic in low resource settings. The aim of this study was to (1) translate, adapt and validate the EMpowerment of PArents in THe Intensive Care-Neonatology (EMPHATIC-N) questionnaire in two languages in Ethiopia (2) explore parents' satisfaction with the care received in the NICUs in three hospitals; and, (3) explore socio-demographic characteristics and level of the NICU influence on the EMPATHIC-N domains. Methods: This was a cross-sectional multicenter study. Participants were recruited from three different NICUs in Ethiopia upon discharge. We reduced the original EMPATHIC-N instrument to 38 items, culturally adapted and validated it in two local languages. Confirmatory Factor Analysis (CFA) was applied to verify the factor structure of the questionnaire, investigating the relationship between items and the five latent domains. Single item scores and the aggregate scores of the domains were investigated across NICUs and in the sample overall. Differences in the distribution of the domain scores were tested according to socio-demographic participants' characteristics. The scores of four general questions about overall experience and satisfaction were investigated in relation to the participant's characteristics and NICU levels. Qualitative data were collected using four open-ended questions and a synthesis of results was provided. Results: Almost all the parents answered to the questionnaire (92%, n = 386). Questionnaire items on satisfaction on average scored more than four. The highest mean scores were obtained for Parental participation (median: 5.17; iqr: 4.67–5.62), while they were lower for Organization/Hospital environment (median: 4.67; iqr:4.33–5.17). Different levels of parent satisfaction were observed across the NICU levels showing a statistically higher satisfaction in level II NICU compared to the other levels. Education, place of residence and length of stay were associated with parental satisfaction and experience. Conclusion: This study validated two Ethiopian versions of the EMPATHIC-N questionnaire to assess parents' experience and satisfaction during their child's stay in the NICU. The differences found across the three levels of NICU suggest the need to further investigate the determinants of satisfaction.